Membrane-based Decentralized Wastewater Treatment and Reuse in Icelandic Scenario - Sif Guðjónsdóttir 1995- (2021)
Globally, the freshwater demand is constantly growing in the world, causing water scarcity in many regions. Meanwhile, the quantity of untreated wastewater is continuously increasing, leading to decreased water quality. To minimize the adverse effects of wastewater on the environment and public health, it must be treated to meet discharge standards prior to being released into the environment. In Iceland, ∼24% of municipal wastewater was not treated, and the remaining municipal wastewater is treated only by primary screen and settling. As conventional biological process (secondary treatment) is not suitable in Iceland due to cold climate, a feasible solution through membrane technique is proposed in this study. Gravitydriven membrane (GDM) filtration of wastewater has been increasingly studied due to their low cost, low maintenance and the ability to have stabilized flux with minimal cleaning. In this study, reactor performance (organic and nutrient removal) and membrane performance (flux, membrane resistance and reclaimed water quality) will be illustrated in GDM systems for wastewater treatment under different operation conditions (biocarriers packing ratio, membrane cleaning protocols). The permeate was collected and used as irrigation water for planting. The results revealed that the permeate irrigated plants met the EU and WHO standards for all except the pH regularly exceeding the recommended amount. The quality was highly comparable to the tap watered plants. Finally, cost analysis with respect to population density (10-5000 people) predicts the total cost over 15 years is estimated to be ∼ 1,000 - 300,000 USD (∼ 123,000 - 38,400,000 ISK). Eftirsókn eftir fersku vatni er stanslaust að aukast í heiminum, sem ýtir undir vatnsskort á mörgum svæðum heims. Á sama tíma er magn skólps samfellt að aukast líka í heiminum, sem gæti leitt til vatnsskorts og að gæði vatns almennt muni minnka. Til að reyna að minnka áhrifin sem skólp hefur á umhverfið og almenna heilsu, þá er ætlast til þess að það uppfylli ...